PERLINDUNGAN KONSUMEN ATAS PENGGUNAAN ALAT TIMBANGAN DI PASAR TRADISIONAL (STUDI PADA PASAR PEDURUNGAN KOTA SEMARANG) - Taufikurrohman, Wafir Lana Dzia Ul Aulia (Universitas Negeri Semarang, 2024)
Traders in traditional markets are responsible for ensuring that every consumer right is well fulfilled. In this research, consumer rights protection is linked to the use of weighing scales to ensure accuracy in transactions. The condition and results of the scales have a significant impact on the process of giving and receiving goods. Therefore, it is important for traders to always ensure that the measuring instruments used are well calibrated and there is no fraud in the weighing process. This research is an empirical juridical study with a sociological jurisprudence approach using qualitative methods. Researchers used primary and secondary data. Data validity techniques used triangulation. Data analysis techniques were done in four stages: data collection, data reduction, data presentation, and conclusion. The research results show that: (1) Traders' understanding in Pedurungan Market, Semarang City about the use of weighing scales and calibration is good, but the cleanliness of the weighing instruments used is still lacking. Some consumers have experienced getting goods that do not match the agreed-upon weight. (2) Supervision of measuring instruments by the Legal Metrology Unit of Semarang City is carried out regularly. Calibration of weighing scales is done at Pedurungan Market, Semarang City, once a year. The conclusions of this research are: (1) Consumer legal protection in Pasar Pedurungan, Semarang City, is not effective, there are inconsistencies related to consumer rights in Article 4 letters (b), (g), and (h) of the Consumer Protection Law. (2) Supervision of measuring instruments by the Legal Metrology Unit is not effective yet due to limitations in the unit's working area, low penalties for business operators, lack of budget, lack of awareness among business operators in complying with the law.